Audit partner tenure, audit firm tenure, and discretionary accruals: Does long auditor tenure impair earnings quality? - CHEN, Chih-Ying (Institutional Knowledge at Singapore Management University, 2008)
Mandatory audit partner relation has been adopted in some countries while audit firm rotation is still being debated in many places. Most of the extant research on the relation between auditor tenure and earnings quality provides evidence at the audit firm level. However, since audit firm tenure is correlated with partner tenure and audit firm rotation is more costly than partner rotation, it is important to know whether earnings quality is related to audit firm tenure, partner tenure, or both. We investigate this issue using a sample of Taiwanese companies for which the audit report must be signed by two partners with their names disclosed in the report. Using performance-adjusted discretionary accruals as a proxy for earnings quality, we find that the absolute and positive values of discretionary accruals decrease significantly with partner tenure. After controlling for partner tenure, we find that [ABSTRACT FROM AUTHOR]